2013
DOI: 10.12968/ijpn.2013.19.7.341
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an educational pain management programme on nurses' pain knowledge and attitudes in Kenya

Abstract: The PMP appears to be effective in improving nurses' pain knowledge and attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
3
35
0
Order By: Relevance
“…A previous study highlighted the knowledge deficits and negative attitudes of the nurses toward postoperative pain at the ordinary nursing compared to the positive improvement in the clinical competency regarding pain assessment and administration of analgesics after pain education as evidenced by higher KASRP tool score (17). While the difference in total knowledge scores between pre-test and post-test was significant, no significant difference was found between post-test and follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study highlighted the knowledge deficits and negative attitudes of the nurses toward postoperative pain at the ordinary nursing compared to the positive improvement in the clinical competency regarding pain assessment and administration of analgesics after pain education as evidenced by higher KASRP tool score (17). While the difference in total knowledge scores between pre-test and post-test was significant, no significant difference was found between post-test and follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…However, they have a moral responsibility to provide the best clinical care in pain relief (25). The nurses' awareness and attitude play an important role in the implementation of an effective pain management process (26) and the results of previous studies showed that training programs in the field of pain significantly enhance the nurses' knowledge and attitude toward pain (27,28). Training in intensive care units should encourage critical care nurses (CCNs) to understand and confidently use pain assessment tools (16).…”
Section: Introductionmentioning
confidence: 99%
“…That improvement could result from the feedback they received during the individual clinical support sessions, which they said it helped them to enhance their pain management skills. Other studies found that pain management CE had a positive effect on nurses' knowledge (Abdalrahim, Majali, Stomberg, & Bergbom, 2011;AlReshidi, Long, & Darvill, 2018;Keen et al, 2017;Machira, Kariuki, & Martindale, 2013;Marceau, 2009;McNamara, Harmon, & Saunders, 2012). For example, a recent systematic review of the impact of educational programs on nurses' post-operative pain management for children (AlReshidi, Long, & Darvill, 2018) found nine studies showing a significant improvement of nurses' knowledge, with eight of them demonstrating good evidence.…”
Section: Discussionmentioning
confidence: 99%